العلاقات العامة في الصحف الالکترونیة الکوردیة ودورها في نشر المواطنة الرقمیة لدی الشباب الجامعي – طلبة اقسام الاعلام فی الجامعات الحکومیة انموذجا - رمضان, عمر احمد; القرداغي, لانه صابر محمد سعيد (Sulaimani Journal for Humanities, 2022)
The subject of digital citizenship is one of the important topics that need to conduct many studies on it at the various educational, social, political, legal, communication and media levels. With the principles and axes of digital citizenship, and if public relations in the Kurdish press institutions attach importance to publishing topics about digital citizenship and its axes within the Kurdish electronic newspapers. The researchers used the descriptive survey method in this study, and they adopted a deliberate sample of students from the media departments at the Universities of Sulaymaniyah and Salah al-Din by distributing a questionnaire to them that was built specifically for this topic. The main conclusions of the study were summarized as follows: 1. Digital citizenship is the extent to which the citizen bears responsibility and self-censorship from the use of new media in general and electronic newspapers in particular, in a way that guarantees his rights and fulfills his duties towards his community. 2. Although the Kurdish electronic newspapers do not pay attention to raising awareness and publishing about digital citizenship in the required way, the limited interest in this field focuses more on the issues of communication with others, and the least interest in electronic newspapers is the focus of achieving psychological and social security, which is a matter of concern. 3. The public relations departments or their substitutes in the electronic newspapers do not have a positive role in urging interest in digital citizenship issues, whether by providing advice to the senior management in these institutions or directing journalists to take care of these issues.